Social inequalities and youth: racial issues under reflection - Wenczenovicz, Thaís Janaina; MARTINS DA SILVA, ANA CAROLINA; RECKZIEGEL, JANAINA (International Journal for Innovation Education and Research, 2022)
The struggle against social inequalities in Brazil has been the center of analysis in several areas of knowledge. Scholars, public managers, researchers, and public policymakers strive to diagnose and implement measures to reduce inequalities in the Brazilian context. Among the multiple forms of manifestation of such inequalities, the social markers of gender, race, and social class are the most investigated. However, color or race occupies a central space in most of the debates given the process of the socio-historical constitution of Brazil. In this debate, besides the aspects that are related to the Brazilian development process characteristics, whose dynamics have produced erasures and silencing throughout the country’s history, black youth are among those included. As a consequence, the partial inclusion of the black, brown, or indigenous populations in this process has translated into higher levels of economic and social vulnerability, with greater incidence in some communities. The present reflection analyzes the impact of the social racial marker among the black Brazilian youth. The bibliographical-investigative methodological procedure is used.